1982
DOI: 10.1038/ki.1982.26
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated pressure natriuresis in hypertensive rats

Abstract: We studied the isolated blood-free perfused nonclipped kidneys from the 2-kidney Goldblatt hypertensive rat model (GHR) to evaluate intrinsic excretory responses to changes in perfusion pressure. We examined kidneys from 10 control rats (in vivo systolic BP 110 +/- 3.6 mm Hg), from 9 rats with nonmalignant hypertension (HBP) (in vivo systolic BP 158 +/- 6.5 mm Hg), and from 5 rats with malignant HBP (in vivo systolic BP 183 +/- 6.4 mm Hg). We found that at all levels of perfusion pressure, the renal vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…It is also well established that the renin-angiotensin system (RAS) can modulate the slope of the pressure-natriuresis mechanism and, when activated, it can lead to a marked suppression of the pressure-natriuresis relationship [17][18][19]. Despite our knowledge, so far it has not been demonstrated that impairment of the pressure-natriuresis mechanism really precedes the development of ANG IIdependent forms of hypertension; all available studies [7][8][9][11][12][13][14][15] have revealed a blunted pressure-natriuresis relationship in ANG II-dependent forms of hypertension only in rats that already exhibited a hypertensive phenotype.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also well established that the renin-angiotensin system (RAS) can modulate the slope of the pressure-natriuresis mechanism and, when activated, it can lead to a marked suppression of the pressure-natriuresis relationship [17][18][19]. Despite our knowledge, so far it has not been demonstrated that impairment of the pressure-natriuresis mechanism really precedes the development of ANG IIdependent forms of hypertension; all available studies [7][8][9][11][12][13][14][15] have revealed a blunted pressure-natriuresis relationship in ANG II-dependent forms of hypertension only in rats that already exhibited a hypertensive phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been demonstrated that the slope of the pressure-natriuresis relationship can be substantially influenced by alterations in the basal levels of angiotensin II (ANG II) and it has been shown that ANG II-dependent models of hypertension exhibit a suppression of the pressure-natriuresis relationship that is implicated to play a role in the pathophysiology of hypertension in these models [7][8][9][10][11][12][13][14][15][16][17][18]. According to the hypothesis proposed by Guyton et al [19], the impairment of the pressure-natriuresis mechanism should precede the development of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, alterations in tubular ion reabsorption and reduced ability to autoregulate RBF and GFR were detected in this model (15,33). It has been suggested that these alterations may contribute to the compromised ability of the nonclipped kidney to maintain normal sodium excretion at normotensive blood pressure (BP) and to the suppression of pressure-natriuresis (32,34,37). However, the mechanism(s) underlying this impairment are still poorly understood.…”
mentioning
confidence: 92%
“…To investigate the roles of glomerular filtration and basolateral uptake in D catabolism further, we used the isolated perfused kidney technique. The preparation and perfusion ofisolated kidneys used in these studies are similarto those reported by us previously (16,17). Male Sprague-Dawley rats, which weighed between 210 and 320 g (259±17) and were maintained on regular rat chow and tap water ad libitum, were anesthetized with an intraperitoneal injection ofpentobarbital sodium (Nembutal, Abbott Laboratories, North Chicago, IL), 6-7 mg/100 g body wt.…”
Section: Methodsmentioning
confidence: 62%